(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2026)
The cost-benefit analysis performance of weaner and grower rabbits fed processed sunflower (Helianthus annuus) seed meal (SFSM) and diets treated with enzymes in the research area was assessed. Nine diets (T1, T2, T3, T4, T5, T6, T7, T8, and T9) were administered to 72 rabbits in a completely randomized manner employing a 3x3 factorial configuration. Treatments T1, T2, and T3 had 0% inclusion rate of SFS meal and 0, 150, and 250 ppm of the enzyme. These diets were designed to be isocaloric (2500 kcal/kg, ME) and isonitrogenous (15%). All management protocols were adhered to produce grower and weaner rabbits. During the weaner phase, there were significant differences (P<0.05) in the average daily intake of feed, protein, and energy between levels. In contrast to 77.48g, 1532g, and 255.18g in 0% SF and 78.76g, 15.45g, and 25.56g in 10% SFSM, the highest values were 80.36g, 10.46g, and 262.73g in 20% SFSM. The 250ppm (15.85g) enzyme had a significantly (P<0.05) higher protein intake than 0ppm (15.49g) and 15.54g, which were not statistically (P>0.05) different from each other. The sunflower seed meal (SFSM)-based diet enhanced with an enzyme affected rabbit production economics. Rabbits fed 20% sunflower seed meal showed much better weight growth, revenue, and net income than rabbits fed 0% and 10% sunflower seed meal. The feed conversion ratio, cost per kilogram of weight gain, and cost of production per kilogram of weight gain were significantly (P<0.05) lower in rabbits fed 20% compared to those fed other diets. The 10% and 20% sunflower seed meal treatments, respectively, had significantly higher total feed consumption than the control diet (P<0.05). Int. J. Agril. Res. Innov. Tech. 15(2): 147-153, Dec 2025